Digital Accounting Dynamics: Unmasking Disruption and Gauging Its Impact on Financial Paradigms - ALNAIMAT, Mohammad Ahmad; MALYUGA, Natalya; SHEVCHUK, Volodymyr; KHMELIUK, Alona; NAIDENKO, Oleksii (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).17, 2025)
The study provides the empirical analysis of the impact of disruptions in accounting on the financial paradigms of 20 large Ukrainian companies for 2019-2023. The aim of the research is to analyse and explain how these disruptions affect financial performance indicators, such as Return on Assets (ROA), company stability, and market value. The research employed a panel data model, where the dependent variable is the financial performance of the companies and disruptions in accounting are the independent variables. The data were collected from publicly available financial statements, audit reports, and macroeconomic indicators. The study applied a fixed-effect and random-effect regression model to measure the relationship between disruptions in accounting and financial indicators. Company size, industry type, and other macroeconomic conditions ( e.g ., Gross Domestic Product (GDP) growth) are control variables. Disruptions in accounting have a significant negative impact on financial performance, including restatements, reporting delays, and qualified audit opinions, which causes a decrease in ROA. GDP growth is a macroeconomic factor that positively affects financial performance, while company size mitigates the negative impact of accounting accuracy on performance. The results show that accurate and timely financial reporting is important for maintaining investor confidence and financial stability. This study is one of the first studies to examine how disruptions in accounting affect Ukrainian companies, provides an up-to-date conceptual understanding of the relationship between financial reporting practices and financial performance in a transformational economy.